StockMaster simulator / Nor Hamiza Mohd Noor ... [et al.] - Mohd Noor, Nor Hamiza; Asbullah, Nurul Farzana; Hairi Annuar, Syazana Ezzati; Tujang, Anatasha Alfiera; Muhammad Rasli, Irdina Hani (Universiti Teknologi MARA, Kedah, 2023)
Introducing StockMaster, a simulator website that offers a game that follows the real time market data, virtual trading platform where users can learn, practise, and understand Islamic finance-based stock market simulation tactics without risking real money. This simulator also offers community because users can conduct virtual online video chats with other users in its own chat room. Many people are hesitant to invest or enter the market due to them lacking the necessary expertise. This Stock Market Simulator provides a realistic virtual trading experience to connect theory and practise so that users can develop successful investment strategies. The uniqueness of this Stock Market Simulator is that it offers a comprehensive and user-friendly platform that simulates the real stock market. Real-time market data, trading algorithms, and interactive features will make it more engaging. Among the distinctive features that are attempted to be highlighted in the game design is the restriction of Riba (Interest), Gharar (Uncertainty) and Haram (Prohibited) activities. Moreover, room chat and online video calls allow players to have meaningful conversations, share their experiences, and make lasting connections. The stock market welcomes the participation of individuals of all ages, backgrounds, and financial knowledge, hence creating a stock community. However, our focus is primarily on college students and individuals who are interested in learning about trading and investment that adheres to Islamic principles Additionally, StockMaster's FAQ provides answers for common questions and provides quick access to information. Apart from helping users learn about handling stocks and investments, it is also a risk-free practice that can improve investor skills. Lastly, StockMaster also complies with Islamic principles, so Muslim investors can assure that they are not involved in prohibited activities.